Analysis of The Self-Confidence of The Athletes of Sumedang - Dicky M Fahrul Rozi; Ayi Suherman; Tedi Supriyadi (Universitas Negeri Semarang, 2026)
Confidence is one of the most important psychological aspects in rock climbing because athletes have to face various challenges, such as altitude, the difficulty level of the trail, and the pressure during training and competition. This study aims to analyze the confidence of rock climbing athletes from Sumedang Regency and identify the factors that influence it. This study uses a qualitative approach with a descriptive method. The data collection technique was carried out through observation and in-depth interviews with four rock climbing athletes who actively train in nature lovers organizations in Sumedang. The data obtained was then analyzed descriptively to describe the real conditions experienced by athletes regarding their confidence level. The results of the study show that in general the athletes have a fairly good level of confidence. This can be seen from their readiness before climbing, the courage to make decisions when facing challenging routes, and the ability to control emotions when at height. Athletes also show an open attitude in evaluating performance after climbing. Athletes' confidence is influenced by two main factors, namely internal factors and external factors. Internal factors include confidence in one's abilities, training experience, positive mindset, and courage to face fear. Meanwhile, external factors include support from coaches, teammates, family, and the availability of training facilities. In addition, some obstacles that can reduce athletes' confidence include nervousness during competitions, fear of heights, pressure from opponents who are considered stronger, and limited training facilities. Based on the results of the research, it can be concluded that the confidence of rock climbing athletes is not formed instantly, but through a continuous training process, competition experience, and support from the surrounding environment.